Tiang Rohomoni: Memaknai Simbol Budaya Berbasis Agama di Gedung Gereja Pniel, Tuhaha, Maluku - Pattiasina, Sharon Michelle O. (FIKRAH, 2022)
This article explores the meaning of the symbol of the Pillar of Rohomoni as a support for the roof of a church building given by Rohomoni as a Muslim community to Christians in Tuhaha. The method used in this research is qualitative with descriptive type. This research uses interview techniques, snowball sampling, and literature studies. The results of the study found that the awarding of the Tiang Rohomoni to the people in Tuhaha was based on pela ties. Tiang Rohomoni represents the identity of pela Rohomoni and Tuhaha as a form of brotherhood that is not limited by religion and culture. The Pillar of Spirit is a symbol that also presents a collective awareness for the people of the two countries to maintain a relationship that helps and supports each other. The pillar is also interpreted as supporting and strengthening the brotherly ties between the two countries.